Pre-Aksumite And Aksumite Agricultural Economy At Ona Adi, Tigrai (Ethiopia): First Look At A 1000-Year History - Datasets - Meresa, Yemane; D'Andrea, Catherine; Lancelotti, Carla; Beldados, Alemseged; Ruiz Giralt, Abel (My University, 2023)
This repository contains the results datasets of the article Pre-Aksumite and Aksumite agricultural economy at Ona Adi, Tigrai (Ethiopia): first look at a 1000-year history submitted to the journal African Archaeological Review.
Keywords: Datasets; Pre-Aksumite; Aksumite Agricultural Economy